Modelagem para identificação de indicadores de eficiência energética para edificações e plantas industriais - Buccieri, Gilberto Paschoal [UNESP] (2014)
This dissertation describes a method for the identification and weighting of indicators of sustainable performance for evaluating the energy efficiency of industrial facilities. Taking as a backdrop some industrial companies based in the Paraiba Valley / SP, it was proposed a list of indicators for assessing energy efficiency criteria, which provides an important reference for mapping, comparison, evolution and appropriate investment for the evaluation of decision makers. The research method consisted of performing a comprehensive literature review and the application of two surveys involving experts and decision makers in the area. The data were modeled from the application of cluster analysis and the method of Analytic Hierarchy Process (AHP) tools to weigh indicators identified, reducing the degree of subjectivity in the analysis of these opinions and seeking levels of intensity targets. The size of the samples is sufficient to support search results, which were validated for consistency analysis of the AHP. The proposed method can also be extended to develop the weighted indicators for other regions